2014
DOI: 10.1002/glia.22649
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ten‐eleven translocation hydroxylase family proteins and 5‐hydroxymethylcytosine in oligodendrocyte differentiation

Abstract: The ten-eleven translocation (TET) family of methylcytosine dioxygenases catalyze oxidation of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) and promote DNA demethylation. Despite the abundance of 5hmC and TET proteins in the brain, little is known about their role in oligodendrocytes (OLs). Here, we analyzed TET expression during OL development in vivo and in vitro, and found that three TET family members possess unique subcellular and temporal expression patterns. Furthermore, the level of 5hmC ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 56 publications
4
60
3
Order By: Relevance
“…Additionally, we observed dynamic changes in TET protein levels with oligodendroglial maturation and oxidative stress in vitro, suggesting important developmental and environment-dependent epigenetic alterations in these cells. Similar results were observed in vivo where alterations in TET1, TET2, and TET3 proteins accompanied oligodendroglial maturation in the developing CNS (Zhao et al, 2014). Differences between OPCs and mature oligodendrocytes were reported for other epigenetic marks such as HDAC1-a known repressor of transcriptional activation (Liu and Casaccia, 2010) which is increased in the mature cells and associated with their more compact chromatin structure.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Additionally, we observed dynamic changes in TET protein levels with oligodendroglial maturation and oxidative stress in vitro, suggesting important developmental and environment-dependent epigenetic alterations in these cells. Similar results were observed in vivo where alterations in TET1, TET2, and TET3 proteins accompanied oligodendroglial maturation in the developing CNS (Zhao et al, 2014). Differences between OPCs and mature oligodendrocytes were reported for other epigenetic marks such as HDAC1-a known repressor of transcriptional activation (Liu and Casaccia, 2010) which is increased in the mature cells and associated with their more compact chromatin structure.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, oligodendrocytes constituting the myelin sheet also exhibit dynamic age-related changes in their epigenome. TET proteins catalyzing the conversion of 5mC to 5hmC show dynamic alterations during oligodendroglial maturation in the developing CNS (Zhao et al, 2014). Furthermore, at the difference from their progenitor cells, mature oligodendrocytes usually present compact chromatin structure and increased histone deacetylase 1 (HDAC1) expression (Liu and Casaccia, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic expressions of DNA methyltransferases and ten-eleven translocation enzymes (TETs) in the oligodendroglial lineage suggested that DNA methylation and hydroxymethylation are essential for oligodendrocyte differentiation [17,18]. Indeed, TET1, TET2, and TET3 have been shown to be necessary for oligodendrocyte differentiation in vitro [18]. Recently, a whole-genome transcriptome and methylome analysis comparing OPCs and oligodendrocytes revealed that DNA methylation is inversely correlated with gene expression during developmental myelination.…”
Section: Introductionmentioning
confidence: 99%
“…The ten-eleven translocation (TET) family of proteins are responsible for the oxidation of 5mC into 5-hydroxymethylcytosine (5hmC) (Zhao et al, 2014), and whilst 5mC is typically associated with gene silencing effects, 5hmC is associated with an increase in gene expression (Coppieters et al, 2014). In addition, it has been found that TET can also covert 5mC into 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC) (Ito et al, 2011).…”
Section: Demethylationmentioning
confidence: 99%